An unsuitable bride - Feather, Jane.; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 2012)
In order to inherit his uncle's fortune, Peregrine Sullivan must marry a fallen woman and finds the perfect candidate in Alexandra Douglas, who, determined to destroy the cousin who stole her family's money, rebuffs his advances.
Only desperation would drive a lady to disguise herself in hopes of employment, but the twenty thousand pounds that their father promised beautiful Alexandra Douglas and her invalid younger sister has vanished into the hands of the greedy cousin who inherited the estate. Alexandra, in search of justice, embarks on an elaborate charade to infiltrate Combe Abbey, her ancestral home, and secretly take the money back. Peregrine, visiting the Abbey, is intrigued by a woman whose mind matches his on every level. Who is this middle-aged spinster with a young woman's eyes and a youthful step that even a limp cannot disguise? Sensing some scandalous secret, Perry assumes the lady would delight in being rescued. But his efforts are rebuffed; Alexandra will take care of herself and her sister, thank you very much. Can Perry court the daring and independent young woman, win her heart, and be the last brother to wed?--Publisher.
Keywords: Man-woman relationships -- Fiction; Inheritance and succession -- Fiction; Sisters -- Fiction; Historical fiction; Love stories